PRE-MATURE MARRIAGE PRACTICES IN TREVOR NUNN'S LADY JANE: A SOCIOLOGICAL APPROACH - SUMANTO , ETIKANINGTYAS (2007)
The problem of this study is "what are the reasons underlying pre-mature marriage practices of Jane in Lady Jane viewed from sociological approach" and the aim of this study is to analyze the movie based on its structural elements. The research is conducted by using qualitative method. In this method, the research uses two data sources, namely primary and secondary data sources. The primary data is Lady Jane movie directed by Trevor Nunn and David Edgar and Chris Bryant as the screen writer. The secondary data sources are books and internet website, which are related to the analysis. Technique of the data collection is library research. Based on the analysis, the writer draws some conclusions as follows: Trevor Nunn criticizes social structure of English society that is dominated by the upper class and also creates the character of Jane to symbolize the attitude of the upper class that there are practices of pre-mature marriage in the England Kingdom. The reasons underlying premature marriage practices of Jane are: In the social aspects, that the parents of Jane and Guilford want to get the high social status to give Jane marriage with Guilford. In the economic aspects, and also they want to get the high economy level. In the political aspects, they want to get the power in the Kingdom, and the last in the religious aspects, they want to dominated England with the Protestant Religion although English at that time is dominated by the Catholic Religion.